How proudly they wave. Flags of the fifty states - Haban, Rita D. (Minneapolis Lerner Publications Company, 1989)
In this book, Rita Haban intriduces you to the 50 state flags. She tells the stories of their origins and explains the historical meaning of each emblem. Clear, colorful, detailed, illustrations, supplied by the Flag Research Center in Winchester, Massachusetts, show the flags of each state.
Keywords: Country Studies